2009
DOI: 10.1029/2009jd012008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal characteristics of the relationship between daily precipitation intensity and surface temperature

Abstract: [1] Past studies have argued that the intensity of extreme precipitation events should increase exponentially with temperature. This argument is based on the principle that the atmospheric moisture holding capacity increases according to the Clausius-Clapeyron equation and on the expectation that precipitation formation should follow accordingly. We test the latter assumption by investigating to what extent a relation with temperature can be observed intraseasonally in present-day climate. For this purpose, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
187
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 33 publications
(40 reference statements)
16
187
3
Order By: Relevance
“…A number of statistical studies have revealed the increase of extreme precipitation intensity with temperature on the basis of percentiles defined for each temperature range, although the rate of increase may deviate from the CC relationship (Berg et al 2009Lenderink and van Meijgaard 2010;Utsumi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of statistical studies have revealed the increase of extreme precipitation intensity with temperature on the basis of percentiles defined for each temperature range, although the rate of increase may deviate from the CC relationship (Berg et al 2009Lenderink and van Meijgaard 2010;Utsumi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a warmer future world, understanding the local and regional implications of changes in the hydrological cycle is critical to planning for water security (Oki and Kanae, 2006). Dynamical regional climate models (RCMs) have been used to assess climate change impacts on spatial distributions of rainfall (Kilsby, 2007), seasonal changes to rainfall (Kendon et al, 2010), and changes to rainfall intensity (Berg et al, 2009) and frequency (Mailhot et al, 2007) at spatial scales relevant to water managers.…”
Section: Introductionmentioning
confidence: 99%
“…The next step is to separate the dataset into seasonal sets in order to take into account the meteorological seasonality. Berg et al (2009) focused on the data of July to characterize the scaling in summer and the data of January for the winter time with the argument that the trends are the strongest for these periods. This paper follows the same approach but extends the period to 3 months in order to increase the amount of considered data and capture the full season.…”
Section: Methodsmentioning
confidence: 99%
“…Above 50°N, the strength of the association becomes even stronger. Berg et al (2009) showed that the dependence between temperature and precipitation was seasonally conditioned. In addition, Berg and Haerter (2011) analyzed the P-T scaling for different precipitation types in Germany.…”
Section: Introductionmentioning
confidence: 99%